2012
DOI: 10.1111/jac.12007
|View full text |Cite
|
Sign up to set email alerts
|

Deep Roots are Pivotal for Regulating Post‐Anthesis Leaf Senescence in Wheat (Triticum aestivum L.)

Abstract: Root activity plays a dominant role in grain filling in cereal crops. However, the importance of deep roots for regulating post-anthesis leaf senescence is not clearly understood in wheat (Triticum aestivum L.). In this study, we used 32 P tracing to estimate the difference in wheat root activity at soil depths of 30 and 70 cm and the root restriction method to investigate the effects of vertical distribution of deep roots on leaf senescence, with non-restricted plants as controls. Recovery of radioactive 32 P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 26 publications
0
10
0
2
Order By: Relevance
“…Assays of the antioxidant enzyme activities were measured as described by Kong et al (2013b , c ). The flag leaves and glumes were harvested at 0, 8, 16, 24, and 32 DAA, immediately frozen in liquid N 2 , and then stored at –80°C until experimental analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Assays of the antioxidant enzyme activities were measured as described by Kong et al (2013b , c ). The flag leaves and glumes were harvested at 0, 8, 16, 24, and 32 DAA, immediately frozen in liquid N 2 , and then stored at –80°C until experimental analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Here, the average root depths for sites were used for the calculations, with the intent to reproduce the conditions of limited input data access on farms. For the calculation of maximum (potential) water depletion from layers of the crop root zone, an empirical approach was used, based on literature data (e.g., Kong et al, 2013), previous studies (Haberle and Svoboda, 2012;Svoboda and Haberle, 2014a), and field observations of apparent depletion of soil water. Before long, depletion of water is shifted to deeper sparsely rooted subsoil layers when the upper zones are exhausted.…”
Section: B Crop Root Depth and Depletion Of Water From The Root Zonementioning
confidence: 99%
“…It is evident that the approach for a solution must be complex. An optimal root system and the utilization of the water reserve from the root zone are recognized as important factors in the effort (Himmelbauer et al, 2008;Kirkegaard et al, 2007;Kong et al, 2013;. Further, deep roots absorb nitrate and other nutrients leached from top soil, an important function in the effort for reduction of water pollution (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…It is a process in which plant tissues or organs move toward functional decline or death. If the crop senescence is rapid, the physiological and biochemical metabolisms of the entire plant change, photosynthesis is seriously reduced, assimilates are insufficient, and grain filling is affected (Kong et al, 2013). Studies have found that early senescence can reduce the plumpness of rice and wheat grain, thereby resulting in a yield loss of more than 20% (Zhang et al, 1998).…”
Section: Introductionmentioning
confidence: 99%